Exercise with TENS does not augment gains in balance and strength for dancers - Davis, L. A.; Carzoli, J. P.; Feka, K.; Nelson, C.; Enoka, R. M. (Journal of Electromyography and Kinesiology, 2021)
Electrical stimulation modulates sensory feedback and improves motor performance, at least for individuals with compromised sensorimotor function. The purpose of this study was to determine the effectiveness of a 4-wk intervention with transcutaneous electrical nerve stimulation (TENS) at improving strength and balance in dancers. Nineteen dancers completed a timed, single-leg balance test, the Y-balance test, and contractions with the hip flexor and knee extensor muscles to assess maximal strength and force steadiness. They completed 4-wks of moderate-intensity bodyweight exercises (3x/wk) and were pseudo-randomized to either a Treatment or Sham group in a single-blind design. The Treatment group received constant TENS over the hamstring muscles during the exercises, whereas the Sham group was exposed to a brief TENS current. The data were pooled due to few significant between-group differences from before to after the intervention. Most outcome measures significantly improved: hip extensor muscles were stronger (P = 0.01), time stood on a single-leg with eyes closed increased (P = 0.02), and the distance reached during the Y-balance test increased (P = 0.001). The improvement in scores on the Y-balance test exceeded the minimal clinically significant change. Twelve sessions of moderate-intensity bodyweight exercises improved muscle strength and balance in experienced dancers. The addition of TENS, however, did not augment the gains in function.